SPE/DOE Improved Oil Recovery Symposium 1996
DOI: 10.2118/35455-ms
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Production From A Rich Gas Condensate Reservoir

Abstract: Increased interest in gas condensate reservoir which exhibit complexities due to the production of gas, condensates and many times an in-situ oil phase has been observed. As expected, there are definite production problems and exploitation concerns which are at issue with gas condensate reservoirs, or reservoirs which exhibit a combination of gas condensate and oil characteristics. In studying reservoirs of this type, there are three main areas which must be adequately addressed in order to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The literature is replete with detailed discussions on formation damage (1)(2)(3)(4)(5)(6)(7)(8) . This paper does not address different types of damage which can occur during conventional drilling, completion and production operations, but concentrates solely on issues associated with condensate liquid dropout.…”
Section: Formation Damage Issues In Gas Condensate Reservoirsmentioning
confidence: 99%
“…The literature is replete with detailed discussions on formation damage (1)(2)(3)(4)(5)(6)(7)(8) . This paper does not address different types of damage which can occur during conventional drilling, completion and production operations, but concentrates solely on issues associated with condensate liquid dropout.…”
Section: Formation Damage Issues In Gas Condensate Reservoirsmentioning
confidence: 99%
“…In his study, he revealed that mobility increase is primarily controlled by capillary number and interfacial tension. Thomas et al 4 and Bourbioux et al 5 suggested that the fluid phase behaviour and fluid flow in the rock depend upon the degree of retrograde condensate accumulation, interfacial tension and mobility (relative permeability).…”
Section: Introductionmentioning
confidence: 99%